Antibiotic Use before Chlamydia and Gonorrhea Genital and Extragenital Screening in the Sexually Transmitted Infection Clinical Setting - Dukers-Muijrers, Nicole H. T. M. (Antimicrob Agents Chemother, 2014)
Background antibiotic use (i.e., administration of antibiotics not directly related to Chlamydia trachomatis or Neisseria gonorrhoeae infections) has been associated with a lower prevalence of genital C. trachomatis infection in a clinical setting. Associations with specific antibiotic types or with N. gonorrhoeae are lacking. Here, we assessed the prevalence of antibiotic use, the different classes and agents used, and their association with a subsequent sexually transmitted infection (STI) clinic C. trachomatis and N. gonorrhoeae test result. At our STI clinic, we systematically registered whether antibiotics were used in the past month (in 29% of the cases, the specific antibiotic agent was named). Patients were screened for urogenital C. trachomatis and N. gonorrhoeae; a third of them were also screened for anorectal and oropharyngeal C. trachomatis and N. gonorrhoeae. The proportion of antibiotics used and their association with C. trachomatis and N. gonorrhoeae prevalence were assessed for heterosexual men, men who have sex with men (MSM), and women. During 14,775 clinic consultations, antibiotic use was reported by 12.2% (95% confidence interval [CI], 11.7% to 12.7%), i.e., 14.8% of women, 8.6% of heterosexual men, and 11.6% of MSM. The most reported antibiotics were penicillins, tetracyclines, and macrolides, respectively. The prevalence was 11.0% (95% CI, 10.3% to 11.3%) for C. trachomatis and 1.9% (95% CI, 1.7% to 2.1%) for N. gonorrhoeae. Only tetracycline use was associated with a lower C. trachomatis prevalence (3%). Overall antibiotic use was associated with lower anorectal C. trachomatis prevalence in MSM only (odds ratio, 0.4; 95% CI, 0.2 to 0.8). STI clinic visitors commonly report recent antibiotic use. Even in a country with low antibiotic consumption, tetracycline use impacted C. trachomatis prevalence, while there was a notable absence of association with azithromycin.